2020
DOI: 10.1021/acs.iecr.0c00896
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Engineering Improved d-Glucose/Xylose Cofermentation of Yarrowia lipolytica

Abstract: Background: Yarrowia lipolytica is considered as a promising biorefinery chassis for production of microbial lipids, the important precursors of advanced biofuels. Unfortunately, wild Yarrowia lipolytica is unable to consume xylose, the major pentose in lignocellulosic hydrolysates. A recombinant strain Yarrowia lipolytica yl-XYL+ can utilize xylose to produce microbial lipids efficiently, but its xylose uptake is severely delayed in the presentence of D-glucose. Therefore, it is critical to develop cofermenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The resulting strains promise improved utilization of xylose in the production of chemical compounds and fuel ( Wei et al, 2020a , b ; Sun et al, 2021 ). Additional metabolic engineering approaches ( Ledesma-Amaro et al, 2016 ; Rodriguez et al, 2016 ; Wu et al, 2019 ), strain mating ( Li and Alper, 2020 ), lab adaptive evolution ( Zhou et al, 2020 ) and the use of artificial chromosomes have all been used to enhance xylose utilization. Although it appears that Y. lipolytica utilizes arabinose in a similar way to xylose, only a few studies have investigated arabinose fermentation by this yeast ( Tsigie et al, 2011 ; Ryu and Trinh, 2018 , 2021 ; Spagnuolo et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The resulting strains promise improved utilization of xylose in the production of chemical compounds and fuel ( Wei et al, 2020a , b ; Sun et al, 2021 ). Additional metabolic engineering approaches ( Ledesma-Amaro et al, 2016 ; Rodriguez et al, 2016 ; Wu et al, 2019 ), strain mating ( Li and Alper, 2020 ), lab adaptive evolution ( Zhou et al, 2020 ) and the use of artificial chromosomes have all been used to enhance xylose utilization. Although it appears that Y. lipolytica utilizes arabinose in a similar way to xylose, only a few studies have investigated arabinose fermentation by this yeast ( Tsigie et al, 2011 ; Ryu and Trinh, 2018 , 2021 ; Spagnuolo et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The higher affinity for glucose with respect to other carbon sources available in the medium is a well-known process, already documented for many oleaginous species due to the carbon catabolite repression [40]. This mechanism leads, in some cases, to diauxic growth phenomena that affect the metabolism of the secondary sugars and further limits the conversion efficiency during the fermentative process [41]. Some authors also found that the slow transport rate of xylose limits the downstream pathway; consequently, the enhancement of the transport rate is necessary for improving the cell growth rate and the xylose conversion efficiency [42,43].…”
Section: Yeast Performance In Synthetic Media Under Different Carbon ...mentioning
confidence: 97%
“…Thus, as the energy demand and serious environmental concerns increase, the technologies including torrefaction, catalytic conversion, gasification, and hydrothermal liquefaction (HTL) have attracted more and more attention and have developed rapidly in recent years. A variety of reactions, including hydrogenation, oxidation, deoxygenation (hydrodeoxygenation, decarboxylation and decarbonylation), catalytic cracking, dehydrogenation, aromatization, reforming, pyrolysis, ketonization, and so on have been achieved. Various products including biochar, bio-oil, hydrogen, aromatics, CO 2 , CO, CH 4 and other gaseous hydrocarbons have been obtained. …”
mentioning
confidence: 99%